Pain relief optimization in dental cases (PRODENT) - Kamantigue, Romeo; Tecson, Elizabeth; Zafra, Alex.
Pain is the singular sensory experience that human use to identify the disease. The science of dental medicine (dentistry) primarily exists maybe because of pain i.e., tootache. Dentistry is always associated to pain and become almost synonymous terms. Most dental cases are in need of analgesics to control pain after tooth extraction. Prescription of analgesics such as NSAIDs, (Non-Steroidal Anti-Inflammatory Drugs) are common among dentists. Among the NSAIDs, mefenamic acid is particularly used for mild to moderate pain. A phase 4 clinical trial was conducted to evaluate the efficacy of a fast-acting preparation of mefenamic acid with sodium lauryl sulfate (Ponstan SF 500 mg.) in the immediate reduction of pain intensity among dental patients who have undergone simple tooth extractions. the study was an open, non-comparative trial. Selected dentists all over the Philippines were asked to fill-up a standard case report form. A total of 901 patients with a mean age of 30 years were enrolled. Fifty eight percent (58%) were females and forty-two percent (42%) were males. Dentists were advised to administer mefenamic acid with sodium lauryl sulfate immediatelt when the patients start to feel pain. Subsequently, the patients were advised to take the drug three times a day for atleast 3 days preferably taken after meals. Eighty six percent (86%) of patients reported pain relief after drug intake within 30 minutes (majority of which occured within 15 minutes - 38.9%). Pain assessment of patient using a Visual Analogue Scale showed no pain by as much as 96.5% compared to 0.9% no response to treatment after an hour of drug intake. The dentists' overall assessment of clinical response was very good to excellent in 80.2% of patients after an hour of drug intake and 88.4% after 3 days of treatment. Adverse events were minor and only one drug-related case was reported.
Keywords: Mefenamic acid; Pain relief